1996
DOI: 10.1088/0022-3727/29/6/034
|View full text |Cite
|
Sign up to set email alerts
|

Plasma formation during solid-body irradiation by microwaves and its application for localizing the energy input

Abstract: Problems associated with the thresholds for plasma production (and connected with it, the nonlinearity of microwave energy release) during irradiation of complex metal - dielectric targets by microwaves in a deep vacuum or in a high-pressure gas were studied. The discovered effect of the low threshold for plasma formation, for which no adequate model exists, may find a number of applications, in particular, in quasi-stationary current generation, gas-discharge rocket engines and microwave soldering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The results of this paper, along with results of the previous paper [14] testify to the feasibility of the scheme based on surface non-self-sustained discharge shown in figure 2.…”
Section: Discussion Of Experimental Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The results of this paper, along with results of the previous paper [14] testify to the feasibility of the scheme based on surface non-self-sustained discharge shown in figure 2.…”
Section: Discussion Of Experimental Resultssupporting
confidence: 70%
“…The microwave energy release is accompanied by efficient and rapid gas heating. Two direct consequences of this effect are the target heating [14] and the mechanical recoil momentum acquired by the target.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (see, e.g. [25][26][27]) have shown that the contact surface between a metal and a dielectric has a very low threshold for excitation of sparks (micro-plasmas) in microwave fields, and the probability of sparking depends only weakly on gas pressure. This plasma production mechanism may explain why low electron currents in the waveguide exist even at the maximum microwave powers attainable in the device and why the electron background current exists even when the wall surface is coated with soot.…”
Section: Discussion Of Experimental Resultsmentioning
confidence: 99%
“…The right (edge) waveguide section was held at atmospheric pressure and equipped with the matched load 5 to realize the regime of a travelling electromagnetic wave in all sections of the coaxial line and to keep the power reflection coefficient very low (less than 0.25%). To reduce the possibility of the appearance of microsparks at the metal-dielectric interface [30,31], the windows were positioned in the widest portion of the coaxial waveguide, where the microwave electric field is the weakest. Furthermore, to reduce the density of the plasma that can result from the microsparks, the joint between the window and the inner electrode was sealed by a narrow circular groove.…”
Section: Methodsmentioning
confidence: 99%